Online vs Offline, New Age of Reading! - Chaudhari, Sumit (International Journal of All Research Education and Scientific Methods (IJARESM), 2022)
The rise of online reading has piqued the interest of researchers, educators, and parents all over the world in how it compares to traditional reading. The central idea of this research paper is to discover How Reading Books Promotes Language Development Around the World. This article investigates research on the links between language and later reading, environmental factors related to language learning, and interventions developed in various countries to encourage parents of young children to read. This research is both qualitative and quantitative. The primary data was gathered by sending them a detailed and structured questionnaire via Google Forms.Three significant moderators were discovered during the analyses: (1) time frame: the advantage of paper-based reading increased in time-constrained reading compared to self-paced reading; (2) text genre: the advantages of paper-based reading were consistent across studies using informational texts or a mix of informational and narrative texts, but not those using only narrative texts; (3) publication year: the benefit of paper's reading increased over time. This research will help us to know how people are adapting the new technology and to know what are the advantages and disadvantages while reading books and news, information, current affairs, and facts.
ISME
Keywords: Reading; social media; E-books; Paperback; Audiobook